A Seamless Gene Deletion Method and Its Application for Regulation of Higher Alcohols and Ester in Baijiu Saccharomyces cerevisiae. (9th May 2019) - Li, Ping; Ge, Junling; Gao, Yingying; Wang, Jianhui; Zhang, Cuiying; Xiao, Dongguang
Abstract : The security of engineering Saccharomyces cerevisiae is becoming more focused on industrial production in consideration of the public concern regarding genetically modified organisms. In this work, a rapid and highly efficient system for seamless gene deletion in S. cerevisiae was developed through two-step integration protocol combined with endonuclease I-SCEI expression. The factors affecting the frequency of the second homologous recombination were optimized, and studies indicated that the mutant strains with 500 bp direct repeats and that have been incubating in galactose (0.5 g/100 mL) medium at 30°C and 180 r/min for 24 h permit high frequency (6.86 × 10 −4 ) of the second homologous recombination. Furthermore, DNA sequence assays showed only self-DNA in native location without any foreign genes after deletion using this method. The seamless gene deletion method was applied to the construction of the engineering strains with BAT2 (encoding aminotransferase) deletion and ATF1 (alcohol acetyltransferases) overexpression. The mutants exhibited significant effects on higher alcohol reduction and ester improvement after Baijiu fermentation. The engineered strains can be used in industrial production in security, thereby meeting the requirements of modern science and technology.